Soil erosion modeling using RUSLE and GIS on Cameron highlands, Malaysia for hydropower development - Teh, Soo Huey (2011)
Verkefnið er unnið í tengslum við Háskóla Íslands og Háskólann á Akureyri Sedimentation is one of the major problems in the hydropower scheme in Malaysia. Cameron Highlands is known to have one of the worse if not the worst sedimentation problem in Malaysia. Uncontrolled deforestation and indiscriminate land clearing for agricultural, housing development and road construction resulted in widespread soil erosion over the land surface of Cameron Highlands leading to sedimentation of the rivers and of the Ringlet Reservoir. The objective of this thesis is to determine the mean annual soil loss rate using the RUSLE model for the Upper Catchment of Cameron Highlands for the years 1997 and 2006. Data such as rainfall pattern, soil type, topography, cover management and support practice were utilized for soil modeling using the integration of RUSLE and ArcGIS. The sub-catchments of Telom, Kial and Kodol, Upper Bertam, Middle Bertam, Lower Bertam, Habu, Ringlet and Reservoir catchments were studied. The sub-catchment of Plau’ur was excluded from this study because data from the region was not sufficient. Sediments were detached and transported from the upper catchment and were eventually deposited in the Ringlet Reservoir. The sediment yield of the Ringlet Reservoir was predicted to be 282,465.5 m3/ year for 1997 and 334,853.5 m3/ year for 2006 from this study. This number is expected to increase with time as agriculture activities and deforestation continues to take place. Hence, the life expectancy for the dead storage was decreased tremendously because of the increasing sediment yield with time compared to the design life expectancy of the dead storage. The drastic situation in Ringlet Reservoir suggests that if nothing is done, the reservoir will lose its entire storage in the next three to five years. In the immediate and medium term, it is expected that any effective strategy for management of the sediments would have to be based on the ‘concentrate and remove’ approach, in which most practical and effective ...